A Review of Targeted Therapies for Monogenic Epilepsy Syndromes - Zimmern, Vincent; Minassian, Berge; Korff, Christian (Frontiers in Neurology, 2022)
Genetic sequencing technologies have led to an increase in the identification and characterization of monogenic epilepsy syndromes. This increase has, in turn, generated strong interest in developing “precision therapies” based on the unique molecular genetics of a given monogenic epilepsy syndrome. These therapies include diets, vitamins, cell-signaling regulators, ion channel modulators, repurposed medications, molecular chaperones, and gene therapies. In this review, we evaluate these therapies from the perspective of their clinical validity and discuss the future of these therapies for individual syndromes.